Efficacy of neoadjuvant, adjuvant, and perioperative immunotherapy in non-small cell lung cancer across different PD-L1 expression levels: a systematic review and meta-analysis - Zhang, Zhenlong; Lin, Yuchen; Chen, Shuchen (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors, particularly anti-PD-1/PD-L1 monoclonal antibodies, have transformed non-small cell lung cancer (NSCLC) treatment. This meta-analysis evaluates the efficacy of neoadjuvant, adjuvant, and perioperative immunotherapy in resectable NSCLC, stratified by PD-L1 expression levels.MethodsWe conducted a meta-analysis of 10 randomized controlled trials (RCTs) involving 11 articles, focusing on pathological complete response (pCR), major pathological response (MPR), event-free survival (EFS), and overall survival (OS). These outcomes were stratified by PD-L1 expression levels (<1%, ≥1%, 1-49%, ≥50%).ResultsImmunotherapy significantly improved pCR (OR=4.96, 95% CI=2.88–8.57 for PD-L1<1%; OR=9.58, 95% CI=6.32–14.53 for PD-L1≥1%), MPR (OR=2.86, 95% CI=1.97–4.16 for PD-L1<1%; OR=7.39, 95% CI=4.59–11.88 for PD-L1≥1%), and EFS (HR=0.80, 95% CI=0.70–0.92 for PD-L1<1%; HR=0.53, 95% CI=0.45–0.62 for PD-L1≥1%) across all PD-L1 subgroups. Greatest benefits were observed in PD-L1≥50% subgroup, with ORs for pCR and MPR, and HRs for EFS, showing consistent improvements. OS benefits were significant in PD-L1≥1% patients (HR=0.62, 95% CI=0.49–0.79 for PD-L1≥1%) but uncertain in PD-L1<1% cohorts (HR=1.11, 95% CI=0.86–1.44 for PD-L1<1%). Immunotherapy in perioperative setting demonstrated robust efficacy, with significant pathological response and EFS benefits across all PD-L1 subgroups.ConclusionThis meta-analysis supports immunotherapy within perioperative care for resectable NSCLC, emphasizing PD-L1 expression as a predictive biomarker. Future studies should optimize patient selection and clarify immunotherapy’s role in different treatment settings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025644497, identifier CRD42025644497.